RATIONALITY OF PRESCRIBING ANTIBIOTICS TO PATIENTS AT THE HEALTH CENTER TELKOMEDIKA CLINIC, YOGYAKARTA - Dwi Puspita Ekasari; Dwi Hastuti (Jurnal Kesehatan Tambusai, 2022)
Excessive and inappropriate use of antibiotics in some cases can cause antibiotic resistance problems, increase treatment costs, and side effects of antibiotics. To prevent the emergence of antibiotic resistance, it is necessary to rationalize the administration of antibiotics. The purpose of this study was to determine the rationality of prescribing antibiotics at the Telkomedika Health Center Clinic in the period October-December 2020. This study used a descriptive observational method. Retrospective data collection used 160 samples of prescriptions and medical records of patients with a diagnosis of bacterial infection and a prescription for antibiotics. The data were analyzed descriptively based on rationality of prescribing including the right diagnosis, the right indication, the right choice of drug and the right dose, the right way of administering the drug, the right duration of drug administration, the right patient with theguidelines Drug Information Handbook, then calculated in percentage form and presented in tabular form. Research results The rationale for prescribing antibiotics to patients at the Telkomedika Health Center Clinic in Yogyakarta for the period October - December 2020 is 100% Correct Diagnosis, 100% Correct Indication, 100% Correct Selection of Drugs, 100% Correct Dosage, 100% Correct Method of Drug Administration, 100% Correct Duration of Drug Administration. These results indicate that the prescription screening conducted at the Telkomedika Health Center Clinic in Yogyakarta has been carried out very well and according to the quality standards that have been set. Keywords : rationality, antibiotics, prescribing